Analisis Pelaksanaan Dan Pengelolaan Perpajakan Di Kecamatan Pangkalan Kerinci, Kabupaten Pelalawan - Ardinata, Kaisar Rezky; Marta, Fitri Yul Dewi (Peneliti.net, 2026)
This study aims to analyze the implementation of tax administration and the level of taxpayer compliance in the working area of the Primary Tax Office (KPP) of Pangkalan Kerinci, as well as to identify the challenges and opportunities in tax management faced by the institution. This research uses a qualitative approach with a descriptive method, where data is collected through literature studies, documentation, and observation of programs and activities carried out by KPP Pratama Pangkalan Kerinci. The results show that the tax office has implemented various initiatives to improve the efficiency and effectiveness of tax services, such as the